Methodological Approaches to Online Serbian Heritage Language Instruction - Ana Krstić; Branimir Stanković (Languages)
In this paper, we propose adequate methodological approaches for Serbian as a heritage language based on the critical analysis of the existing Serbian Ministry of Education’s Curriculum for Serbian as a foreign language. This curriculum is recommended for use in Serbian heritage language education; however, it has been shown to be insufficiently effective in the classroom. The methods in question should benefit heritage speakers the most, such as communication-based methods and form-focused instruction, which enhance metalinguistic awareness. Additionally, we suggest an integrative model of teaching as we believe that cross-cultural approaches positively impact both types of students.